(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Women are more likely to operate their own businesses because of their individuality and strength of character. Female entrepreneurs have a leg up in the marketplace thanks to their innovative product ideas, which might be a reflection of their marketing success. As a fundamental component of market strategy, marketing performance is both a significant management problem and an essential component of company success. Women-Owned Textile Businesses in the Ernakulam District were the focus of this research, which aimed to examine how marketing innovations affected their performance.